Enroller Experience and Parental Familiarity of Disease Influence Participation in a Pediatric Trial - Jeff E. Schunk; Kammy K. Jacobsen; Dilon Stephens; Amy Watson; Cody S. Olsen; T. Charles Casper; Nicole S. Glaser; Nathan Kuppermann (Western Journal of Emergency Medicine, 2021)
Introduction: Acquiring parental consent is critical to pediatric clinical research, especially in interventional trials. In this study we investigated demographic, clinical, and environmental factors associated with likelihood of parental permission for enrollment in a study of therapies for diabetic ketoacidosis (DKA) in children. Methods: We analyzed data from patients and parents who were approached for enrollment in the Pediatric Emergency Care Applied Research Network (PECARN) Fluid Therapies Under Investigation in DKA (FLUID) trial at one major participating center. We determined the influence of various factors on patient enrollment, including gender, age, distance from home to hospital, insurance status, known vs new onset of diabetes, glycemic control (hemoglobin A1c), DKA severity, gender of the enroller, experience of the enroller, and time of enrollment. Patients whose parents consented to participate were compared to those who declined participation using bivariable and multivariable analyses controlling for the enroller. Results: A total of 250 patient/parent dyads were approached; 177 (71%) agreed to participate, and 73 (29%) declined. Parents of patients with previous episodes of DKA agreed to enroll more frequently than those with a first DKA episode (94.3% for patients with 1–2 previous DKA episodes, 92.3% for > 2 previous episodes, vs 64.9% for new onset diabetes and 63.2% previously diagnosed but no previous DKA). Participation was also more likely with more experienced enrollers (odds ratio [95% confidence interval] of participation for an enroller with more than two years’ experience vs less than two years: 2.46 [1.53, 3.97]). After adjusting for demographic and clinical factors, significant associations between participation and both DKA history and enroller experience remained. Patient age, gender, distance of home from hospital, glycemic control, insurance status, and measures of DKA severity were not associated with likelihood of participation. Conclusion: Familiarity with the disease process (previously diagnosed diabetes and previous experience with DKA) and experience of the enroller favorably influenced the likelihood of parental permission for enrollment in a study of DKA in children.